Influência da fotobiomodulação na viabilidade e proliferação de células-tronco do ligamento periodontal humano cultivadas na superfície de filmes de ácido polilático - Lira, Jadson Alexandre Silva (2021)
Polylactic acid (PLA) is a biomaterial with diverse biomedical applications and has been a promising scaffold in tissue engineering mainly due to its biocompatibility, easy manipulation and low cost. Low-level laser irradiation (LLLI) has been shown to be a powerful tool to promote in vitro biostimulation in several cell types. The aim of this study was to evaluate the effectiveness of photobiomodulation with LLLI on the viability and proliferation of human periodontal ligament stem cells (hPDLSC) cultured on PLA scaffolds. PLA films were produced by solvent casting method and the surface topography was evaluated by scanning electronic microscopy (SEM) and atomic force microscopy (AFM). hPDLSC were isolated, characterized and cultured on the PLA films. Two groups were evaluated: Control - non irradiated; and Laser - irradiated with diode laser (InGaAIP) with wavelength of 660 nm, power of 30 mW, and a single dose of 1 J/cm² with radiation emitted continuously. Cell viability analyzes were performed 24 and 48 hours after irradiation using the the Alamar Blue biochemical assay and Live/Dead assay. Cell cycle events were assessed by flow cytometry and cell-biomaterial morphological interaction was evaluated by SEM. The films produced showed a flat and regular surface, with the occasional presence of small pores and an average roughness of 59.381 nm. The results of Alamar Blue assay showed a greater cell metabolic activity in irradiated group compared to control at 24 (p<0.05) and 48 h (p<0.001), which was confirmed in the Live/Dead assay by a higher density of viable cells in the Laser group. In the analysis of the cell cycle, the Laser group showed an increase of cells in the G2/M phase compared to the Control group (p <0.001). SEM images showed a higher cell density in the irradiated group, with maintenance of cell morphology. Taken together, the findings of this study demonstrated that photobiomodulation has the ability to increase the viability and proliferation of periodontal stem cells cultured on PLA scaffolds, which may contribute to the development of new studies using this protocol in periodontal tissue engineering.